Studi Validitas dan Reliabilitas Mindfulness in Teaching Scale Indonesia - Rullyta Nadia Khairani; Surya Cahyadi; Hery Susanto (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study was aimed to examine the validity and reliability of the Mindfulness in Teaching Scale in Indonesia (MTS-I). This research was a quantitative research. Data were collected from teachers of elementary, secondary, and high school in Bandung (n=244) using convenience sampling. Confirmatory factor analysis (CFA) was conducted to test the two factor structures of MTS-I, Pearson product moment to test concurrent validity, and Cronbach’s alpha to test the internal consistency. Results confirmed the validity and reliability of the model. MTS-I had the same structure with the original one. MTS-I had 13 valid and reliable items which were divided into two dimensions, interpersonal mindfulness and intrapersonal mindfulness. MTS-I demonstrated construct validity with good-fit index. Furthermore, regarding concurrent validity, positive correlations were obtained between MTS-I subscales with teacher efficacy, and negative correlations were obtained between MTS-I subscales with teacher stress.